Exploring the Effectiveness and Challenges of Community Rehabilitation Service Programs for Children with Developmental Delays: A Qualitative Study from the Perspective of Early Intervention Service Providers in Taiwan - Shu-Jou Sun; Wei-Lin Wang; Wei-Lun Huang; Wei-Sho Ho (MDPI AG, 2024)
This qualitative study aimed to investigate the effectiveness of community rehabilitation programs for children with developmental delays from the perspective of early intervention service providers in Taiwan. Adopting a single-case experimental design (ABM design), this study examined the immediate and sustained effects of interventions on individualized goals during baseline, intervention, and maintenance phases. Additionally, data from interviews with parents, special education teachers, and other participants were collected to understand the challenges and improvement strategies of community rehabilitation programs. Results revealed that community rehabilitation programs for children with developmental delays exhibited both immediate and sustained effectiveness. Challenges faced by parents and professionals differed, with parents having less contact and communication with administrative systems, while professionals experienced more pronounced implementation difficulties during interventions. Moreover, strategies for improving community rehabilitation programs for children with developmental delays should vary for parents and professionals to address inconsistencies in attitudes and strategies among parents and administrative obstacles encountered by professionals.